(REAP) strategy and its role in the development of academic achievement The students of the Institute of Fine Arts (Journal of the College of Basic Education, 2023)
The current research aims to identify the role of the (REAP) strategy in developing the academic achievement of the students of the Institute of Fine Arts in the subject of art criticism. The researcher formulated the research hypothesis: - There are no statistically significant differences at the level of significance (0.05) between the average ranks of the students of the experimental group who studied according to the (R.E.A.P) strategy and between the average ranks of the students of the control group who studied according to the (usual method). ) about their responses to the achievement test of the post-art analysis and criticism subject. The experimental approach was used, and the experimental design was used with two equal experimental and control groups. The total sample of the research was (40) students, (20) students as the experimental group, (20) students as the control group. The researcher prepared the research tool represented by the achievement test, consisting of (25) multiple-choice items, and it was characterized by honesty and stability. The experiment lasted (8) weeks, after applying the tool and using statistical methods in data processing. The results showed that there were statistically significant differences at the significance level (0.05) between the mean scores of the experimental group students who studied according to (REAP strategy) and the mean scores of the control group students who studied according to the (usual method) about their answers to the achievement test. Afterward, in favor of the experimental group. This indicates that the study plans based on the REAP strategy have caused a development in the academic achievement of the students of the experimental group The most important conclusions and recommendations are that the REAP strategy makes the student more capable of understanding the material, because the student in this strategy is the one who thinks, concludes, observes, justifies and interprets, in contrast to the usual methods that do not allow the student to participate in such a way.